Differentiation between glioma recurrence and treatment effects using amide proton transfer imaging: A mini-Bayesian bivariate meta-analysis - Chen, Kai; Jiang, Xi-Wen; Deng, Li-jing; She, Hua-Long (Frontiers in Oncology, 2022)
Background: Amide proton transfer (APT) imaging as an emerging MRI approach has been used for distinguishing tumor recurrence (TR) and treatment effects (TE) in glioma patients, but the initial results from recent studies are different. Aim: To systematically review and quantify the diagnostic performance of APT in assessing treatment response in patients with post-treatment gliomas. Methods: A systematic search in PubMed, EMBASE, the Web of Science was performed to retrieve related original studies. For the single and added value of APT imaging in distinguishing TR from treatment effects TE, we calculated pooled sensitivity and specificity by using Bayesian bivariate meta-analyses. Results: Six studies were included, five of which reported on single APT imaging parameters and four of which reported on multiparametric MRI combined APT imaging parameters. For single APT imaging parameters, the pooled sensitivity and specificity were 0.85 (95% CI: 0.75-0.92) and 0.88 (95% CI: 0.74-0.97). For multiparametric MRI including APT, the pooled sensitivity and specificity were 0.92 (95% CI: 0.85-0.97) and 0.83 (95% CI: 0.55-0.97), respectively. In addition, in the three studies reported on both single and added value of APT imaging parameters, the combined imaging parameters further improved diagnostic performance, yielding pooled sensitivity and specificity were 0.91 (95% CI: 0.80-0.97) and 0.92 (95% CI: 0.79-0.98), but the pooled sensitivity was 0.81 (95% CI: 0.65-0.93) and specificity was 0.82 (95% CI: 0.61-0.94) for single APT imaging parameters. Conclusion: APT imaging showed high diagnostic performance in assessing treatment response in patients with post-treatment gliomas, and the addition of APT imaging to other advanced MRI techniques can improve the diagnostic accuracy for distinguishing TR from TE.